2012
DOI: 10.1002/srin.201100264
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Ferrite/Silicon Nitride Composite Concept Aimed at Automotive Applications

Abstract: This paper presents the investigation of the behavior of a Fe–1.5 wt% Si thin sheet upon plasma‐assisted nitriding at 570°C. It had been confirmed that a very fine and intense precipitation of amorphous silicon nitride occurs as nitrogen diffuses into the sheet. The precipitates, the size of which is comprised between several and several tens of nanometer, display a cubic morphology in spite of their amorphous structure. These cubes adopt a particular morphology in relation to the matrix with their faces paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…These phases were identified as a-Si 3 N 4 and b-Si 3 N 4 , both well known in bulk silicon nitride, although a is said to have a fraction of its nitrogen substituted with oxygen depending on experimental conditions. In much more recent research, it has been shown that during nitriding at 570-580°C, silicon nitride precipitates abundantly in FeSi binary alloys in fine stoichiometric Si 3 N 4 precipitates [1,[4][5][6]. These nanoprecipitates display the odd combination of an amorphous structure with a cuboidal morphology.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These phases were identified as a-Si 3 N 4 and b-Si 3 N 4 , both well known in bulk silicon nitride, although a is said to have a fraction of its nitrogen substituted with oxygen depending on experimental conditions. In much more recent research, it has been shown that during nitriding at 570-580°C, silicon nitride precipitates abundantly in FeSi binary alloys in fine stoichiometric Si 3 N 4 precipitates [1,[4][5][6]. These nanoprecipitates display the odd combination of an amorphous structure with a cuboidal morphology.…”
Section: Introductionmentioning
confidence: 97%
“…This precipitation can notably be exploited to strengthen and lighten sheets of silicon-rich steel [1]. In order to obtain an adequate volume fraction of nitride precipitates, the required nitrogen cannot be introduced during liquid state processing of the alloy due to the limited solubility of nitrogen in liquid iron.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, nitriding studies have been performed on relatively simple iron-based binary alloys, especially in recent years. On the one hand, most work has been done on the alloying element nitride precipitation in ferritic substrates (responsible for enhancing the fatigue resistance), Fe-Al, [8][9][10][11][12] Fe-Cr, [13,14] Fe-Si [15][16][17][18][19][20] and Fe-V, [21,22] and ternary alloys, such as Fe-Cr-C, [12,23] Fe-Cr-Al, [24] Fe-Cr-Ti [25] and Fe-Me-Si. [26] On the other hand, the effect of alloying elements on the formation of the surface iron nitride (c¢-Fe 4 N 1Àx and e-Fe 2 N 1Ày ) compound layer, usually indicated as the ''white layer'' (responsible for improved wear and corrosion resistances), has only recently been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[34,35] After the first demonstration that silicon nitride precipitates in ferrite in a highly unusual amorphous state, [36] only recently have the kinetics of this amorphous silicon nitride precipitation been investigated more extensively. [18][19][20]26] It was shown that the precipitation of amorphous silicon nitride in the ferrite matrix takes place only very slowly because of the large volume misfit, which has to be accommodated upon precipitating silicon nitride in the ferrite matrix. Thus, Si is effectively a weak nitride former, [26] although, from a chemical point of view, Si is a strong nitride-forming element.…”
Section: Introductionmentioning
confidence: 99%
“…Intense work is in progress in recent years in the sphere of obtaining types of ceramics in which properties of oxygen-free substances and oxygen substances will be fused and SiALON are namely such materials [15]- [18].…”
Section: Introductionmentioning
confidence: 99%